Harnessing multiple generated excitons from intermolecular singlet fission of perylene–monoimides in a p-type dye-sensitized solar cell. (15th January 2023) - Papadopoulos, Ilias; Schol, Peter R.; Garcés-Garcés, Jose; Sastre-Santos, Ángela; Fernández-Lázaro, Fernando; Guldi, Dirk M.
Highlights: Perylene-monoimide monomers on p-type semiconductor exhibit singlet fission. Intermolecular singlet fission in the solid state. P-type dye-sensitized solar cells capable of harnessing the power of singlet fission. Transparent p-type NiO semiconductor for transient absorption measurements. Abstract: A perylene-monoimide (PMI) monomer is functionalized with a benzoic acid to support immobilization on copper oxide (CuO) / nickel oxide (NiO) p -type semiconductors in order to construct p -type dye-sensitized solar cells (DSSCs). All devices are fully characterized by means of J-V, electrochemical impedance, and incident photon-to-current conversion efficiency (IPCE) measurements. Their optimization in terms of PMI uptake, iodine / Li + addition and layer thickness lead to efficiencies as high as 0.07 %. For PMIs, the favorable relationship between their respective singlet and triplet excited state energies of 2.36 and 1.12 eV enable thermodynamically driven singlet fission (SF). The strong inter–PMI interactions on the semiconductor surface allow for an efficient and fast intermolecular SF. The formed correlated triplet pair ((T1 )(T1 )) is corroborated by means of time-resolved transient absorption spectroscopy (TAS) and partakes in an interfacially charge injection into the CuO / NiO semiconductors within the p -type DSSCs.